Interleukin-6: A Novel Target for Cardio-Cerebrovascular Diseases - Su, Jian-Hui; Luo, Meng-Yi; Liang, Na-; Gong, Shao-Xin; Chen, Wei; Huang, Wen-Qian; Tian, Ying; Wang, Ai-Ping (Frontiers in Pharmacology, 2021)
Cardio-cerebrovascular disease is a collective term for cardiovascular disease and cerebrovascular disease, being a serious threat to human health. A growing number of studies have proved that the content of inflammatory factors and inflammatory mediators determines the stability of vascular plaque and the incidence of cardio-cerebrovascular event, and involves in the process of Cardio-Cerebrovascular Diseases. Interleukin-6 is a widely used cytokine that causes inflammation and oxidative stress, which would further result in cardiac and cerebral injury. The increased expression of interleukin-6 is closely related to atherosclerosis, myocardial infarction, heart failure and ischemic stroke. It is a key risk factor for these diseases by triggering inflammatory reaction and inducing other molecules release. Therefore, interleukin-6 may become a potential target for the prevention and treatment of Cardio-Cerebrovascular Diseases in the future. This paper is aimed to discuss the expression changes and pathological mechanisms of interleukin-6 in Cardio-Cerebrovascular Diseases, and to provide a novel strategy for the prevention and treatment of Cardio-Cerebrovascular Diseases.